Peran Empati dalam Design Thinking untuk Pembelajaran Efektif pada Pendidikan Pancasila dan Kewarganegaraan - Fazlan Ade Umri; Rahmadani Indah Nasution; Novi Fitriandika Sari; Nurlina Ariani Hrp (Pancasila and Civics Education Journal, 2026)
Abstract: This study aims to analyze the role of empathy in design thinking in enhancing the effectiveness of Civic Education (PPKn) learning. The method used is a qualitative approach with a literature review based on various scientific sources from the last ten years. The findings indicate that empathy is a fundamental element in design thinking, serving as a foundation for understanding students’ needs, experiences, and social contexts. The integration of empathy in Civic Education learning shifts the instructional paradigm from a normative and teacher-centered approach to a more participatory, reflective, and experience-based learning process. In addition, empathy contributes to strengthening students’ civic identity and civic responsibility by enhancing their ability to understand social perspectives and improve collaborative skills. In the context of Society 5.0, this approach is highly relevant in shaping citizens who are inclusive, democratic, and responsible. Therefore, empathy in design thinking plays an important role in improving the quality and effectiveness of more humanistic and contextual Civic Education learning.Keywords: Empathy, Design Thinking, Civic Education (PPKn), Civic Identity, Human-Centered Learning.Abstrak: Penelitian ini bertujuan untuk menganalisis peran empati dalam design thinking terhadap efektivitas pembelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn). Metode yang digunakan adalah kualitatif dengan pendekatan kajian pustaka (literature review) dari berbagai sumber ilmiah 10 tahun terakhir. Hasil kajian menunjukkan bahwa empati merupakan elemen fundamental dalam design thinking yang berfungsi sebagai fondasi untuk memahami kebutuhan, pengalaman, dan konteks sosial peserta didik. Integrasi empati dalam pembelajaran PPKn mampu menggeser paradigma pembelajaran dari yang bersifat normatif dan teacher-centered menjadi lebih partisipatoris, reflektif, dan berbasis pengalaman nyata. Selain itu, empati juga berkontribusi dalam penguatan civic identity dan civic responsibility peserta didik melalui peningkatan pemahaman perspektif sosial dan kemampuan kolaboratif. Dalam konteks Society 5.0, pendekatan ini menjadi relevan untuk membentuk warga negara yang inklusif, demokratis, dan bertanggung jawab. Dengan demikian, empati dalam design thinking terbukti berperan penting dalam meningkatkan kualitas dan efektivitas pembelajaran PPKn yang lebih humanis dan kontekstual.Kata Kunci: Empati, Design Thinking, Pendidikan Kewarganegaraan (PPKn), Identitas Kewarganegaraan, Pembelajaran Berpusat pada Manusia.